Ethiopian mothers' experiences with micronutrient powders: Perspectives from continuing and noncontinuing users. (17th October 2019) - Pelto, Gretel H.; Tumilowicz, Alison; Schnefke, Courtney H.; Gebreyesus, Seifu Hagos; Hrabar, Mélanie; Gonzalez, Wendy; Wodajo, Hana Yemane; Neufeld, Lynnette M.
Abstract: As part of a formative evaluation of a micronutrient powder (MNP) trial in Ethiopia that was organized according to a programme impact pathway model, we conducted in‐depth focused ethnographic interviews with caregivers of children between 6 and 23 months who had accepted to try "Desta, " a locally branded MNP. After stratification into two subgroups by child age, respondents were randomly selected from lists of caregivers who had received MNP from government health workers between 1 and 3 months prior to the interview date. Thirty women who were either currently giving Desta to their child ("continuing users, " n  = 14) or had stopped feeding Desta ("noncontinuing users, " n  = 16) were purposefully recruited from both urban and rural areas in the two different regions where the trial was conducted. Interviews were recorded, transcribed and translated, and coded for both emerging and prespecified themes. On the basis of identifiable components in the caregiver adherence process, this paper focuses exclusively on factors that facilitated and inhibited "appropriate use" and "continued use." For "appropriate use, " defined as the caregiver preparing and child consuming MNP as directed, we identified four common themes in caregiver narratives. With respect to "continued use, " the caregiver providing and child consuming the minimum number of MNP sachets over a recommended time period, our interviews spontaneously elicited five themes. We also examined caregivers' perceptions related to problems in obtaining refills. Attention to caregivers' perspectives reflected in their narratives offers opportunities to improve MNP utilization in Ethiopia, with potential application in other social and cultural settings.